Switching on the Lights for Real-Time Multimodality Tumor Neuroimaging: The Integrated Positron-Emission Tomography/MR Imaging System - Bisdas, S.; Nägele, T.; Schlemmer, H.-P.; Boss, A.; Claussen, C.D.; Pichler, B.; Ernemann, U. (American Journal of Neuroradiology, 2010)
SUMMARY: A recent report of the feasibility of simultaneous PET/MR imaging of the healthy human brain has sparked excitement in the field of neuroimaging because of its potential influence and utility in clinical neuroscience research. The aim of this communication is to discuss the benefits and current drawbacks of the hybrid imaging system and to highlight some perspectives of the new technique for brain neoplasms. 11Ccarbon 1118Ffluorine 18FDGfluorodeoxyglucoseFETfluoroethyltyrosineFLTfluorothymidineFMISOfluoromisonidazoleH2hydrogen 215Ooxygen 1517Ooxygen 17PETpositron-emission tomographyPMTsphotomultiplier tubesSUVstandardized uptake value